Awareness of the Maternal Health Benefits of Lactation Among US Pregnant Women [A30]. (May 2022) - Iwuagwu, Caidon; Chen, Melissa J.; Hoyt-Austin, Adrienne E.; Kair, Laura R.; Fix, Margaret; Schwarz, Eleanor Bimla
Abstract : INTRODUCTION: Rates of breastfeeding in the US remain suboptimal. Public health campaigns encouraging breastfeeding have focused on health benefits for infants, despite over 60 years of data demonstrating breastfeeding reduces maternal risk of breast cancer with more recent data indicating breastfeeding lowers maternal risk of ovarian cancer, diabetes, hypertension and heart disease. METHODS: To assess awareness of the effects of lactation on maternal health, we used social media to recruit a prospective cohort of US-born nulliparous women carrying a singleton pregnancy of 28+ weeks' gestation in 2021. Participants were compensated a $20 gift card for completing an online survey. Institutional review board (IRB) approval was obtained. RESULTS: Of 152 respondents, a family history of breast cancer (9%), diabetes (23%), hypertension (26%), and heart disease (9%) was reported by some; fewer (5%) were diagnosed with gestational diabetes or a hypertensive disorder of pregnancy (2%), and 76% were college educated. Most respondents were aware that breastfeeding benefits infant health; 23% strongly (and 42% somewhat) felt that breastfed babies are healthier than formula fed babies. Most (91%) believed breastfeeding will save their family money. Most strongly (67%) or somewhat (23%) agreed that breastfeeding their baby was important. However, fewer than half were aware that breastfeeding lowers maternal risk of breast cancer (47%), ovarian cancer (32%), diabetes (25%), and hypertension or heart disease (28%). CONCLUSION: Few US pregnant women are aware of the maternal health benefits of breastfeeding. Counseling pregnant women about the beneficial effects of lactation on maternal, in addition to infant, health may help increase breastfeeding rates.